CUSTOMS UNION - THE BASIS OF A COMPETITIVE ENVIRONMENT - Ермекбаева, Б. Ж. (Journal of Economic Research & Business Administration, 2015)
The article investigates the role and importance of the Customs Union in the integration processes. Highlighted the work carried out within the Customs Union on the harmonization of indirect taxation,regulation of currency and monetary operations. The role of the Customs Union as the basis for the formation of Common Economic Space.